Energy-saving algorithm for data centre network based on genetic algorithm. (30th April 2020) - Yang, Shu; Yang, Hua; Chai, Wen; Liu, Zehui
This thesis focuses on network equipments in the data centre which has caused rapidly growth of energy consumption recent years. The switches account for the largest proportion of energy consumption of network equipments, so turning off unneeded switches can reduce energy consumption effectively. Based on this point, we develop a high-efficient routing algorithm based on genetic algorithm (GA) in order to improve energy consumption of network equipments. Genetic algorithm is a kind of a heuristic algorithm which solves the optimisation problem rapidly by imitating the way of the natural selection, but to a certain degree, it reduces accuracy. It is a complicated problem to decide routing path in a short period, so we choose genetic algorithm to achieve our goals. In our simulation, we make some improvements of GA in order to fit our problem and raise the accuracy of its solution.